Deradicalization of Minors Involved in Terrorist Attacks - Eko Nurisman; Winda Fitri; Winsherly Tan (Sekolah Tinggi Hukum Bandung, 2023)
Terrorism as a universal threat to peace has been a huge problem specifically for Indonesia, threatening the fabrics of Indonesian society in collaboration with radicalism, which can reach even minors. To fight this, efforts to eradicate radicalization as an important factor in the spread of terrorism’s influence should be supported with by adequate regulations. Using the normative legal research method, this research analyzes the reality of terrorism and its relation to the existing relevant legal framework in Indonesia. This research finds that terrorism has a wide grip on Indonesian society, especially the youth, due to the spread of radicalism and the weak normative structure surrounding the act of radicalization. Findings and analysis of this research argue that there are possibilities of using the restorative justice approach through the process of deradicalization, according to Indonesia’s ideology, Pancasila.